#GirlGamers, Soldiers, and Public Relations: Analyzing Gender Representation in U.S. Army Esports. (7th January 2022) - Fisher, Jolene; Foust, Joshua
Abstract: While interest in esports is widespread across demographic categories, the gendered norms surrounding video game play have been replicated, resulting in a male-dominated space. Scholars argue that broadening representations of gamers is necessary to normalizing women's presence in esports. As nongaming organizations enter the space, they have a unique opportunity to disrupt established norms through their representations of esports competitors. This study analyzes the representation of U.S. Army Esports (USAE) team members via official social media channels. USAE was created as a public relations tool to engage with a younger audience, redefine the public image of the Army, and recruit soldiers. Using a critical public relations framework and critical discourse analysis, we examine the discourse around gender and esports constructed through USAE's representation of team members and the role of public relations practice in reinforcing or disrupting existing norms.